SOCIOECONOMIC AND DEMOGRAPHIC STUDIES ON ENTREPRENEURIAL INTENTIONS - Agus Aribowo; Popo Suryana; Benny Budiawan; Ezra Karamang (Faculty of Economic and Business, University of Pasundan, 2026)
Entrepreneurship plays an important role in regional economic development; however, entrepreneurial intention does not always translate into entrepreneurial activity, particularly in communities facing socioeconomic constraints. This study examines the influence of socioeconomic and demographic factors on entrepreneurial intention among residents of Cirebon Regency, Indonesia. A quantitative explanatory design was employed using purposive sampling of 183 respondents, and the data were analyzed using multinomial logistic regression. The results show that age, occupation, and education significantly influence entrepreneurial intention (p < 0.05), whereas gender, income, and place of residence do not. Although most respondents reported high entrepreneurial intention, they generally had relatively low educational attainment and income levels. These findings suggest that entrepreneurial intention is shaped more by human capital and work experience than by economic resources alone. The study provides empirical evidence on the role of socioeconomic and demographic characteristics in explaining entrepreneurial intention in a developing regional context.